The Role of E-Commerce Adoption in Driving Business Growth of Micro MSMEs: Evidence from Semarang City - Mellasanti Ayuwardani; Sri Eka Sadriatwati; Rara Ririn Budi Utaminingtyas; Rustono; Irin Mirrah Luthfia (Cita konsultindo, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in Indonesia are currently the backbone of the national economy, contributing 61.07% to the national gross domestic product (GDP) and absorbing 97% of the workforce. Digitalization has become one of the keys to MSME growth. Many micro-enterprise actors are keeping up with technological developments by expanding their businesses through the use of technology, one of which is utilizing e-commerce. This study is an explanatory research. The population consists of micro MSMEs in the city of Semarang, with a total sample of 41 respondents. Data collection was carried out by distributing questionnaires via Google Forms. The results of the study indicate a significant influence of e-commerce adoption on business growth.